Animal detectives and 'Anthropocene noir' in Chloe Hooper's A Child's Book of True Crime. Issue 5 (28th May 2018) - Farrier, David
ABSTRACT: In a recent lecture, Deborah Bird Rose posited the emergence of 'Anthropocene noir', a reality in which 'we, human beings, are all criminals, all detectives, and all victims'. In the Anthropocene there is no single body, culprit, scene or event which definitively identifies the 'crime' of the current extinction crisis. Delocalised in its causes, incalculable and potentially irredeemable in its effects, this crisis is a compelling example of what Ulrich Beck calls global risks, anticipated catastrophes which cannot be delimited spatially, temporally or socially. Via a reading of Chloe Hooper's novel A Child's Book of True Crime as an instance of ironic crime fiction which characterises ecological crimes as at the same time incalculable and urgently in need of recognition, this article will what sort of crime fiction can account for the nature of ecological transgression and its detection in Beck's world risk society, in which the time and scene of the crime cannot be limited to a particular moment or location.